Governing food futures: Towards a 'responsibility turn' in food and agriculture. (January 2022) - Arnold, Nadine; Brunori, Gianluca; Dessein, Joost; Galli, Francesca; Ghosh, Ritwick; Loconto, Allison Marie; Maye, Damian
Highlights: The special issue is on dynamics of responsibility in the context of food systems. Responsibility has growing importance in the context of sustainability transitions. Responsibility changes and depends on institutional conditions. Responsibility has three dimensions: temporal, socio-technical and relational.